Trans-acting aptazyme for conditional gene knockdown in eukaryotic cells - Shan Zhou; Meiyi Chen; Yi Yuan; Yan Xu; Qinlin Pu; Xilei Ai; Shuai Liu; Feng Du; Xin Huang; Juan Dong; Xin Cui; Zhuo Tang (Elsevier, 2023)
Trans-acting hammerhead ribozyme inherits the advantages of being the smallest and best-characterized RNA-cleaving ribozyme, offering high modularity and the ability to cleave any desired sequence without the aid of any protein, as long as the target sequence contains a cleavage site. However, achieving precise control over the trans-acting hammerhead ribozyme would enable safer and more accurate regulation of gene expression. Herein, we described an intracellular selection of hammerhead aptazyme that contains a theophylline aptamer on stem II based on toxin protein IbsC. Based on the intracellular selection, we obtained three new cis-acting hammerhead aptazymes. Moreover, the corresponding trans-acting aptazymes could be efficiently induced by theophylline to knock down different targeted genes in eukaryotic cells. Notably, the best one, T195, exhibited a ligand-dependent and dose-dependent response to theophylline, and the cleavage efficiency could be enhanced by incorporating multiplex aptazymes.